The Effect of Unsafe Actions on Workplace Accidents in the Fabrication Workshop of PT. X - Sholihah, Mazroatus; Budiono, Nugrahadi Dwi Pasca (LPPM Universitas Mohammad Husni Thamrin, 2026)
Background: Workplace accidents in the industrial sector remain a critical issue requiring serious attention, particularly in fabrication workshop environments with high hazard potential. One of the primary contributing factors is unsafe action, defined as unsafe behaviors performed by workers, such as failure to use personal protective equipment (PPE), lack of discipline, and reduced focus during work. These behaviors increase the likelihood of injuries and workplace losses. This study aims to analyze the relationship between unsafe actions and workplace accidents at the Fabrication Workshop of PT. X. A quantitative approach with a cross-sectional design was employed. The sample consisted of 96 respondents selected using simple random sampling based on the Slovin formula. Data analysis using the Chi-Square test yielded a p-value of 0.000 (<0.05) and an Odds Ratio of 9.625 (95% CI: 3.641–25.441), indicating a significant association between unsafe actions and workplace accidents. Workers engaging in unsafe behaviors are at higher risk of experiencing accidents compared to those demonstrating safe practices. Therefore, companies are recommended to strengthen occupational health and safety implementation through JSA evaluation, regular safety briefings, enhanced supervision of work behavior, and consistent application of reward and punishment systems to reduce accident risks.